2014
DOI: 10.1590/s1679-45082014ao3000
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of post-deployment indicators of oral health on the Family Health Strategy

Abstract: Objective To evaluate the evolution of indicators after the implementation of 21 Oral Healthcare Teams in the Family Health Strategy.Methods We used data from outpatient services of Oral Healthcare Teams to evaluate efficiency, access, percentage of absences and emergencies of oral healthcare professionals who worked in the partnership between the Sociedade Beneficente Israelita Brasileira Hospital Albert Einstein and the Secretaria Municipal de Saúde de São Paulo, during the period 2009-2011.Results Percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…When analyzing the expansion of the oral health team (OHT) in the PHC network over a three-year period, one study noticed that, in relation to the total number of appointments, there was a statistically significant reduction during the studied period that was justified by the year of greatest expansion. Nevertheless, the monthly variation was high and, although there was a reduction in the total number of emergency visits, in the vast majority of the months studied, the target of less than 20% of the total number of appointments was not reached [29]. In the ecological study, the differences between the group of services with the highest ratio of emergency and preventive procedures could not be explained by the population coverage provided by the family health team and the ESB [28].…”
Section: Enabling Factors and Gapsmentioning
confidence: 75%
“…When analyzing the expansion of the oral health team (OHT) in the PHC network over a three-year period, one study noticed that, in relation to the total number of appointments, there was a statistically significant reduction during the studied period that was justified by the year of greatest expansion. Nevertheless, the monthly variation was high and, although there was a reduction in the total number of emergency visits, in the vast majority of the months studied, the target of less than 20% of the total number of appointments was not reached [29]. In the ecological study, the differences between the group of services with the highest ratio of emergency and preventive procedures could not be explained by the population coverage provided by the family health team and the ESB [28].…”
Section: Enabling Factors and Gapsmentioning
confidence: 75%
“…When analyzing the expansion of the oral health team (OHT) in the PHC network over a three-year period, one study noticed that, in relation to the total number of appointments, there was a statistically significant reduction during the studied period that was justified by the year of greatest expansion. Nevertheless, the monthly variation was high and, although there was a reduction in the total number of emergency visits, in the vast majority of the months studied, the target of less than 20% of the total number of appointments was not reached[27]. In the ecological study, the differences between the group of services with the highest ratio of emergency and preventive procedures could not be explained by the population coverage provided by the family health team and the ESB[26].…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed in some Brazilian municipalities to analyze the evolution of the indicators after the insertion of the OHT into the FHS showed that, with the increase in the average number of OHT over the years, the indicators of access [62 -64], income, and the percentage of urgencies also increased, and the number of supervised brushings increased considerably [62]. The increase in population coverage by OHT was also related to the reduction of periodontal problems in the elderly [63].…”
Section: Oral Health Indicators After the Oht Implementation In The Fmentioning
confidence: 99%